Performance evaluation of antimicrobial peptide ll-37 and hepcidin and β-defensin-2 secreted by mesenchymal stem cells. Issue 10 (October 2019) - Esfandiyari, Reza; Halabian, Raheleh; Behzadi, Elham; Sedighian, Hamid; Jafari, Ramezan; Imani Fooladi, Abbas Ali
Abstract: Peptides are secreted by different cell types and are trendy therapeutic agents that have attracted attention for the treatment of several diseases such as infections. Antimicrobial peptides exert various mechanisms such as changing cell membrane permeability which leads to inhibition or death of bacterial cells. mesenchymal stem cells (MSCs) are key to produce antimicrobial peptides and to inhibit the growth of pathogens. These cells have been shown to be capable of producing antimicrobial peptides upon exposure to different bacteria. As a result, antimicrobial peptides can be considered as novel agents for the treatment of infectious diseases. The purpose of this review was to investigate the targets and mechanisms of antimicrobial peptides secreted by MSCs. Abstract : Biotechnology; Microbiology; Molecular biology; Proteins, Infectious disease; Mesenchymal stem cells; Antimicrobial peptides; Bacteria